Prompt-based mental health screening from social media text - Santos, Wesley Ramos dos; Paraboni, Ivandré (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2024: Anais do XIII Brazilian Workshop on Social Network Analysis and MiningDO - 10.5753/brasnam.2024.1879, 2024)
This article presents a method for prompt-based mental health screening from a large and noisy dataset of social media text. Our method uses GPT 3.5. prompting to distinguish publications that may be more relevant to the task, and then uses a straightforward bag-of-words text classifier to predict actual user labels. Results are found to be on pair with a BERT mixture of experts classifier, and incurring only a fraction of its training costs.